The immune response against Francisella tularensis live vaccine strain in Lps(n) and Lps(d) mice - Macela, A; Stulik, J; Hernychova, L; Kroca, M; Krocova, Z; Kovarova, H (FEMS immunology and medical microbiology, 1996)
The impact of Lps gene on the course of immune response against subcutaneous infection of mice with Francisella tularensis live vaccine strain was studied. Production and specificity of antibodies, cytotoxic responses of macrophages and NK-cells, spontaneous production ex vivo of cytokines IL-1 alpha, IL-2, IL-4, IL-6, IL-10, IFN-gamma, and TNF-alpha in spleen cell cultures in C3H/HeJ (Lps(d)) mice in comparison with C3H/HeN (Lps(n)) mice were tested. The value of LD(50) was significantly different in the two strains of mice (8.0 x 10(5) cfu for C3H/HeJ versus 4.61 x 10(3) cfu for C3H/HeJ mice after subcutaneous inoculation). The production of NO(2) is also impaired in C3H/HeJ mice in the early intervals after infection. Thus, the defective Lps gene of C3H/HeJ mice influences both the level of innate resistance of mice to F. tularensis live vaccine strain infection and the process of induction and regulation of immune response against this intracellular bacterial pathogen.
Keywords: bakteriální vakcíny; atenuované vakcíny; Mice, Mutant Strains; Antibodies, Bacterial; protilátky bakteriální; makrofágy; Female; cytokiny; tularemie; Vaccines, Attenuated; myši; Mice, Inbred C3H; oxid dusnatý; Mice; myši inbrední C3H; Killer Cells, Natural; Cytokines; zvířata; mutantní kmeny myší; ženské pohlaví; Animals; Tularemia; Bacterial Vaccines; Francisella tularensis; buňky NK; Macrophages; Nitric Oxide